Assessing anxiety symptom severity in Rwandese adolescents: cross-gender measurement invariance of GAD-7 - Niwenahisemo, Lisa Cynthia; Hong, Su; Kuang, Li (Frontiers in Psychiatry, 2024)
Anxiety disorders are among the most common mental health problems experienced by adolescents worldwide because of their evident significant impact on their quality of life and functioning. The generalized anxiety disorder item (GAD-7) was manufactured to identify the severity of self-reported anxiety symptoms. Efforts to address and screen for mental health problems in Rwanda have been limited, and the importance of screening for anxiety disorders is high. The primary aim of this study was to analyze the psychometric properties of the Kinyarwanda version of the Generalized Anxiety Disorder GAD-7, and then test the measurement invariance of the GAD-7 by gender. We used the Rwandese version of GAD-7 among secondary school students in Kigali city (n=1813). Measurement invariance of the GAD-7 across gender and report on anxiety symptom severity prevalence. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to examine measurement invariance. Our findings demonstrated that in the sample of 1813 adolescents aged between 12 and 17 years, generalized anxiety symptoms prevalence rates were higher in females (46.4%) than males (n= 29.8%) GAD-7 demonstrated good reliability and validity coefficients with a Cronbach's α of .077 and KMO and Bartlett test of Sphericity = 0.835. In addition to these psychometric properties, the GAD-7 screening scale had equivalence for configural and metric invariance across groups with excellent fit indices, and we confirmed partial scalar invariance across groups. The GAD-7 can be used in cross-group comparison of prevalence and note that we acknowledge that full scalar invariance is generally difficult to confirm, especially due to gender differences. We recommend that future studies further investigate populations living in rural areas and conduct trials that will focus on anxiety-specific treatment in Rwandan Clinical health care centers to determine the diagnostic accuracy of this screening tool.